Agents of (un)sustainability: democratising universities for the planetary crisis - McGeown, Calum; Barry, John (Frontiers in Sustainability, 2023)
As producers and gatekeepers of knowledge, and as providers of education and training, universities play a key role in the reproduction of unsustainability. This they do, for example, through maintaining (or in some cases actively promoting) research, development and employment links with extractive and polluting industries and by uncritically teaching unsustainable perspectives and practices, including the ‘commonsense’ positive neoclassical economics perspective on the (ecocidal) pursuit of indefinite economic growth. Yet, as highly resourced and influential institutions, universities have an inherently transformative potential, should those resources be redirected and redistributed to progressive social and ecological ends that challenge rather than support the unsustainable status quo. As workers within these institutions, academics and researchers are therefore faced with a choice: to be agents of this reproduction or to be advocates and activists for change. This article argues for the latter. In doing so, it seeks to build on the analysis and demands of emergent movements such as Fossil Free Research, Faculty for a Future and Scientist Rebellion, as well as academic trade unions, in making the case for universities to show leadership on listening to the very science they produce on the planetary emergency, and act accordingly. However, the paper finds that in order to realise these transformative capabilities, universities themselves must undergo transformations to reorient academic practices around social and ecological priorities. To this end, it makes normative and practical arguments from a green political economy perspective for a broad programme of democratisation. It identifies three horizons of democratisation as: (1) Research, (2) Education and (3) Outreach and engagement. Any such processes will of course be difficult, especially given the conservative institutional culture of universities (including the pro-status quo incentive structure academics face in terms of research funding, status and progression and promotion). This article therefore anticipates and argues that this will initially involve individuals or small groups of academics willing to ‘step out of line’ in seeking such transformative and innovative changes.